Psychiatrists should tread cautiously in firearms risk assessment: COMMENTARY… GUNS AND PSYCHIATRY. (January 2020) - Bryant, Robin
SUMMARY: Ann Mortimer's article on gun control and licensing in the UK makes some important points concerning the role of the psychiatrist during the licensing process and the complexities surrounding this. However, the risk-assessment framework (describing low, medium and high risk) that she proposes is problematic.